2013
DOI: 10.1159/000351452
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Angioedema - Occurrence, Clinical Features and Associated Disorders in a Danish Nationwide Patient Cohort

Abstract: Background: The prevalence of acquired angioedema (AAE) is hitherto unknown and, to date, less than 200 patients have been reported worldwide. AAE is associated with lymphoproliferative conditions and autoantibodies against C1 inhibitor (C1INH). Rituximab (RTX) is increasingly used in the treatment of AAE patients. Methods: A nationwide study of AAE patients was performed in Denmark. Clinical features, associated disorders, treatments and outcomes were registered. Results: Eight AAE patients were identified. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 30 publications
4
42
3
4
Order By: Relevance
“…In our cohort, the diagnostic delay turned out to be short, probably due to the selection of patients referring directly to an AE reference center; the median was 2 years, which differs slightly from recent data in the literature [51] .…”
contrasting
confidence: 77%
“…In our cohort, the diagnostic delay turned out to be short, probably due to the selection of patients referring directly to an AE reference center; the median was 2 years, which differs slightly from recent data in the literature [51] .…”
contrasting
confidence: 77%
“…In severe C1-INH-AAE, besides symptomatic therapy treatment of the underlying disease is a sine-qua-non in order to attenuate antibody-production to C1-Inh. Elimination of autoreactive B-cells with anti-CD20 (Rituximab) turned out to be effective (69,70).…”
Section: Treatmentmentioning
confidence: 99%
“…Most data regarding the acquired form of the disease relies on case reports and case series. A recent Danish nationwide study identified only eight patients with AAE, who constituted less than 10% of the C1INH deficiency cohort [3]. The diagnostic delay was on average 1 year and 8 months.…”
Section: Commentarymentioning
confidence: 99%
“…Similarly, a British study showed an average diagnostic delay of 5 years [4]. Many patients with AAE have an underlying lymphoproliferative disorder, ranging from relatively benign causes such as monoclonal B cell lymphocytosis or monoclonal gamopathy of unknown significance to acute B cell leukemia [3,5,6]. AAE might be the presenting symptom [5].…”
Section: Commentarymentioning
confidence: 99%